2018
DOI: 10.1016/s1473-3099(18)30558-9
|View full text |Cite
|
Sign up to set email alerts
|

Scabies control: the forgotten role of personal hygiene – Authors' reply

Abstract: Scabies outbreaks in ten care homes for elderly people: a prospective study of clinical features, epidemiology, and treatment outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 4 publications
2
15
0
1
Order By: Relevance
“…Showering and using cleaning products for personal hygiene remove immature mites from the skin, reducing the possibility of transmission of scabies infection [ 12 ]. The UK National Health Service’s recommendation for keeping the body clean is daily washing of the genitals and bathing or showering at least twice a week [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Showering and using cleaning products for personal hygiene remove immature mites from the skin, reducing the possibility of transmission of scabies infection [ 12 ]. The UK National Health Service’s recommendation for keeping the body clean is daily washing of the genitals and bathing or showering at least twice a week [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…Experimental findings also showed that viability and number of Sarcoptes scabiei was not reduced by hand washing or rubbing hands with alcohol [28]. Scholars sagest such over guessing view might occur due to false impression that substance that are bactericidal or virucidal will be effective against mites [29].…”
Section: Discussionmentioning
confidence: 99%
“…However, hygiene and handwashing do not affect the mite or transmission, 95 and highly effective control has been demonstrated without any measures addressing hygiene or environment (see below), 96 suggesting that associations with situations of poverty and disadvantage are likely due to poor access to healthcare and treatment, or the effects of overcrowding. 21,97 The economic burden of scabies in some areas is thought to be substantial, particularly due to the infestation leading to absence from employment and education, as well as the direct costs of accessing healthcare and repeated treatments ( Figure 3). Economic studies of the costs of scabies infestation and complications are needed to define and advocate for the most cost-effective control strategies.…”
Section: Social and Economic Issuesmentioning
confidence: 99%